2012
DOI: 10.1155/2012/984024
|View full text |Cite
|
Sign up to set email alerts
|

Renal Protective Effect of Xiao-Chai-Hu-Tang on Diabetic Nephropathy of Type 1-Diabetic Mice

Abstract: Xiao-Chai-Hu-Tang (XCHT), a traditional Chinese medicine formula consisting of seven medicinal plants, is used in the treatment of various diseases. We show here that XCHT could protect type-1 diabetic mice against diabetic nephropathy, using streptozotocin (STZ)-induced diabetic mice and high-glucose (HG)-exposed rat mesangial cell (RMC) as models. Following 4 weeks of oral administration with XCHT, renal functions and renal hypertrophy significantly improved in the STZ-diabetic mice, while serum glucose was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Taking these into account, we have shown that CGE was able to completely reverse the progressive loss of glomerular and tubular permeability and functions. Similarly to CGE, traditional Chinese medicine Xiao-Chai-Hu-Tang was found to restore mesangial expansion, basement membrane thickening, glomerular hypertrophy, and tubular damage in T1DM rats [ 30 ] while quinapril, the angiotensin-converting enzyme inhibitor, was also able to restore defective glomerular albumin permeability in experimental diabetic nephropathy rats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking these into account, we have shown that CGE was able to completely reverse the progressive loss of glomerular and tubular permeability and functions. Similarly to CGE, traditional Chinese medicine Xiao-Chai-Hu-Tang was found to restore mesangial expansion, basement membrane thickening, glomerular hypertrophy, and tubular damage in T1DM rats [ 30 ] while quinapril, the angiotensin-converting enzyme inhibitor, was also able to restore defective glomerular albumin permeability in experimental diabetic nephropathy rats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal roles of oxidative stress in the development of aging, cancer, autoimmune disorders, cardiovascular diseases, rheumatoid arthritis, neurodegenerative diseases, and drug-induced liver and kidney injury have been well established. Several studies demonstrated that RB containing herbal formulas, including Da-Chai-Hu-Tang, Xiao-Chai-Hu-Tang and Chai-Hu-Shu-Gan-San, improve oxidative stress in various animal models, including depressive model, atherosclerosis, nephropathy of diabetes and chemical-induced liver injury (Iizuka et al, 1998;Lin et al, 2012;Ohta et al, 1995;Shu-Qi et al, 2010). In line with these findings, purified SS monomers-based studies suggested that both SSa and SSd reverse impaired hepatic activity of superoxide dismutase, improve hepatic antioxidant defense capability, eliminate of ROS, inhibit lipid peroxidation and eventually protect hepatocytes from chloroform-and CCl 4 -induced oxidative stress and liver injury (Fan et al, 2007;Wu et al, 2010).…”
Section: Effects Of Sss On Oxidative Stressmentioning
confidence: 99%
“…fructus . XCHT has been shown to decrease the expression of TGF- β 1, FN, and collagen IV accompanied with increased BMP-7 expression in STZ induced diabetic mice and HG stimulated RMC, which was mediated through decreasing oxidative stress and productions of TGF- β 1, FN, and collagen IV in renal cortex during the development of DN [ 48 ].…”
Section: Applications Of Tcm In Dnmentioning
confidence: 99%